Community-Based Service Learning: Mentoring Scientific Article Writing and Publication in Reputable Journals for Members of the Pohon Baca Community at IAIN Curup - Akhmad Aidil Fitra; Erwin Rochmansyah; Asnaini; Robeet Thadi; Idi Warsah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This community service study examines the implementation of community-based Service Learning as a model for mentoring the writing and publication of scientific articles in reputable journals for members of the Pohon Baca Community at IAIN Curup, Bengkulu, Indonesia. The community faced a critical gap between high writing enthusiasm and limited technical competence in academic publication. Grounded in a three-stage Service Learning framework pre-implementation, implementation, and post-implementation as articulated by Afandi et al the program integrated intensive workshop sessions, writing clinics, and supervised journal-submission processes. One hundred and thirty-five student participants received training in article structure, Mendeley-based reference management, Open Journal System (OJS) navigation, and SINTA/Scopus journal selection. A mixed-methods design combining paired-sample t-tests with thematic analysis was used to assess program outcomes. Results indicate a statistically significant improvement in scientific writing literacy (pre-test mean: 41.7; post-test mean: 73.8; increase: 77.0%; p < .001). In total, 85.9% of participants (n = 116) completed full article drafts, and eight manuscripts were successfully submitted to nationally accredited SINTA-indexed journals. The study demonstrates that Service Learning, when aligned with genuine community needs and supported by multidisciplinary academic mentoring, effectively bridges the university–community divide and generates measurable scholarly outputs. The model is recommended for replication across Islamic higher education institutions seeking to cultivate a sustainable publication culture through community engagement.